Pemanfaatan Rempah Tradisional dalam Teh Celup Khairuntea untuk Mendukung Kesehatan Masyarakat - Hatari, Gunawan; Lumbessy, Abd. Syukur (Program Studi Kehutanan, Universitas Khairun, 2025)
Indonesia is known for its abundant diversity of spices that have been traditionally used as culinary ingredients and herbal medicine. However, the conventional use of spices is increasingly being abandoned due to its lack of practicality. Therefore, the innovation of processing spices into Khairuntea tea bags is expected to provide a solution that promotes a healthy lifestyle while improving the local economy. This community service activity aimed to educate the community on the health benefits of spices as functional beverages, train participants in producing hygienic and standardized tea bags, and enhance product competitiveness through packaging, branding, and digital marketing. The participatory method was applied by engaging the Gambesi Village community in Ternate City over four months. The results revealed a 70% improvement in community knowledge of bioactive compounds in spices, over 80% of participants acquired the skills to produce quality tea bags, and product sales increased by an average of 25–30% through social media and marketplace platforms. Packaging innovation strengthened the local identity of the product, while involving farmers as suppliers created tangible economic impacts. Thus, the development of Khairuntea provides dual benefits by supporting public health and strengthening the local economy.